The Binocular Balance at High Spatial Frequencies as Revealed by the Binocular Orientation Combination Task - Wang, Yonghua; He, Zhifen; Liang, Yunjie; Chen, Yiya; Gong, Ling; Mao, Yu; Chen, Xiaoxin; Yao, Zhimo; Spiegel, Daniel P.; Qu, Jia; Lu, Fan; Zhou, Jiawei; et al. (Frontiers in Human Neuroscience, 2019)
How to precisely quantify the binocular eye balance (i.e., the contribution that each eye makes to the binocular percept) across a range of spatial frequencies using a binocular combination task, is an important issue in both clinical and basic research. In this study, we aimed to compare the precision of a binocular orientation combination paradigm with that of the standard binocular phase combination paradigm in measuring the binocular eye balance at low to high spatial frequencies. Nine normal adults (average age: 24.6 ± 2.0 years old) participated. Subjects viewed an LED screen dichoptically with polarized glasses in a dark room. The method of constant stimuli was used to quantitatively assess the point of subjectively equality (PSE), i.e., the interocular contrast ratio when two eyes are balanced in binocular combination, for stimulus spatial frequencies from 0.5 to 8 cycles/degree. Precision was quantified by the variance (i.e., SE, obtained from 100 bootstrap estimates) associated to the PSE. Using stimuli whose interocular phase difference at the edge of the gratings were matched at 45°, we found that the orientation paradigm provides more precision than the standard binocular phase combination paradigm, especially at high frequencies (experiment 1). Such differences remained when using stimuli that had 3 times larger interocular phase difference (experiment 2) or displayed at 4 times higher stimuli resolution (experiment 3). Our results indicate that a binocular combination tasked based on orientation rather than phase, provides a more precise estimate of binocular eye balance in human adults at high spatial frequencies, thus allowing binocular balance to be assessed within the spatial region where amblyopes are most defective (i.e., high spatial frequencies).